2018
DOI: 10.1002/esp.4441
|View full text |Cite
|
Sign up to set email alerts
|

An entropy based morphological variability assessment of a large braided river

Abstract: The present paper utilizes entropy to investigate variability in the surface areas of sandbars distribution of the Brahmaputra River, India. The intensity entropy disorder index (IDI) was computed for the dry and the post‐monsoon season for a selected reach of the river. The planform disorder index (PDI) was computed to represent the annual scale planform change due to seasonal flood. Finally, annual monsoon and peak flood stream power were evaluated and related to PDI. The results showed that the intensity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Part of the fluvial energy is also stored/absorbed within the system eventually before it initiates a new planform change (Charlton, 2007). A conceptualization of the channel instability in the Brahmaputra River basin integrating the studies of Goswami (1985), Takagi et al (2007), Karmaker et al (2017) and Chembolu and Dutta (2018) is shown in Figure 4b. After the 1950s, the extreme earthquake and series of landslides stimulated high sediment loads completely dominated the morphological processes.…”
Section: Energy Dissipation Processes In a Highly Braided River Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Part of the fluvial energy is also stored/absorbed within the system eventually before it initiates a new planform change (Charlton, 2007). A conceptualization of the channel instability in the Brahmaputra River basin integrating the studies of Goswami (1985), Takagi et al (2007), Karmaker et al (2017) and Chembolu and Dutta (2018) is shown in Figure 4b. After the 1950s, the extreme earthquake and series of landslides stimulated high sediment loads completely dominated the morphological processes.…”
Section: Energy Dissipation Processes In a Highly Braided River Systemmentioning
confidence: 99%
“…In general, channel segmentation, bar erosion and migration are common morphological processes resulting in significant energy dissipation (Chembolu & Dutta, 2018;Dubey et al, 2020). It should also be noted that a considerable amount of energy in a braided river system is utilized through bedform changes and the braided belt width variability (Ashworth et al, 2000;Chembolu & Dutta, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations